FRI0373 The Clinical and Demographic Features of Relapsing Polychondritis: A Nationwide Study. (15th July 2016) - Emmungil, H.; Erden, A.; Küçükşahin, O.; Zengin, O.; Ermurat, S.; Gök, K.; Doğru, A.; Kalfa, M.; Akyol, L.; Erbasan, F.; Çınar, M.; Balcı, M.A.; et al.
Abstract : Background: Relapsing polychondritis (RP) is a rare systemic and inflammatory disease. Objectives: to assess clinical features, management and prognosis in RP. Methods: Retrospective medical records were collected from 16 centers for 37 patients with RP diagnosed by Michet criteria. Data included patients' demographics, clinical features, laboratory findings and outcome. Results: A total of 37 patients, (Male/female=19/18) with a mean disease onset of 45.7±11.8 years and median follow up period is 20 (1–360) months were enrolled. The most common initial complaints and organs involved were showed in table 1 . Mean lead time to diagnose was 28.6±54.3 (0–228) months. Four patients had a known history of cartilage injury before the RP diagnosis (Three goiter operation and 1 resuscitation due to a drowning). Twelve of the patients (32.4%) had also various autoimmune or hematologic diseases. After the diagnosis, moderate or high dose prednisone (n=37, 100%), plus methotrexate (n=15, 40.5%) or azathioprine (AZA) (n=11, 29.7%) or hydroxychloroquine (HQ) (n=3, 8.1%) or cyclophosphamide (CYP) (n=2, 5.4%), or (AZA+ HQ n=3, 8.1%) treatments were initiated. In the case of resistant disease, CYP (n=6, %16.2), tocilizumab (n=2, 5.4%), etanercept (n=1, 2.7%), infliximab (n=1, 2.7%) and bevacizumab (n=1, 2.7%) treatments were given. Due to tracheal stenosis surgery applied to 2 patients, one patient died due to respiratory collapse, 21 patients on remission without any complications, 13 (35.1%) patients had developed tracheal stenosis (n=5, 13.5%), major airway cartilage loss (n=5, 13.5%), auricular collapse (n=2, 5.4%), nasal collapse (n=3, 8.1%), subglottic stenosis (n=2, 5.4%), hearing loss (n=5, 13.5%), vision loss (n=1, 2.7%) and deforming arthritis (n=1, 2.7%). In the univariate analysis, only major airway involvement had a relationship with complication development. (OR 12, 95% CI 1.97–72.8, p=0.007) Conclusions: RP is a rare disease which diagnosis is commonly delayed and lead to cartilage loss. RP developed after trauma in 4 patients, possibly trauma can be blamed as an etiologic factor. Awareness and early diagnosis results with better prognosis Disclosure of Interest: None declared